The Effect of Recruitment on Employee Performance (Case Study at PT. XYZ) - Mintari, Nia; winanti, winanti; Asbari, Masduki; Rizka, Aulia; Ayunita, Dian; Manalu, Lorence (Journal of E-business and Management Science, 2024)
This study discusses how recruitment influences employee performance in a private company in Tangerang City. Reliable and competent human resources are the main factors for competitive advantage, so that the development of Human Resource Competence is one of the key factors for success in achieving the company's vision and mission. The company must be able to understand how best to manage employees who come from different backgrounds, expertise, and abilities so that employees can work according to their expertise and the type of work given. The purpose of the study is to test the implementation of a procedure and to evaluate effectively, efficiently, and economically a system in an effort to achieve company goals. The research method used is a quantitative method. Researchers use primary data using a questionnaire given to 57 employee samples from 1 private company with a 5-point Likert scale directly. The data analysis technique for this study uses SPSS as a statistical method for data processing. From the results of the analysis, the value of the regression equation between X and Y is Y = 11.279 + 0.795X. The constant value a = 11.279 while the regression coefficient figure of 0.795 states that every additional effort (because +) 1 recruitment unit, will increase employee performance by 0.795. The results of testing with simple linear regression show that the Recruitment variable (X) on employee performance (Y) indicated by the R Square value of 50.1%, this shows that the recruitment variable has an effect of 50.1% on employee performance and the rest is influenced by factors other than recruitment. Based on the results of the study, it can be concluded that recruitment has a significant effect on employee performance.